Limitations of Ber-EP4 for distinction of Bowen disease from basal cell carcinoma - Kogut, Marta; Toberer, Ferdinand; Enk, Alexander; Hassel, Jessica C. (Journal of cutaneous pathology, 2016)
Background Diagnostic differentiation between Bowen disease a variant of squamous cell carcinoma in situ (SCCIS) and basal cell carcinoma (BCC) can be difficult on the basis of hematoxylin and eosin (routine) staining in small or fragmented biopsy samples. Ber-EP4 staining is diagnostically reliable for differentiation between BCC and cutaneous squamous cell carcinoma [Dasgeb et al. Biomark Cancer, 5: 7, (2013); Tellechea et al. Am J Dermatopathol, 15: 452 (1993)]. The objective of this study was to determine the usefulness of Ber-EP4 staining for differentiation of SCCIS from BCC. Methods Here, we performed immunohistochemistry with a Ber-EP4 antibody in 76 cases of Bowen type of SCCIS. As positive controls we selected 16 cases of BCC. Results A positive reaction was obtained for Ber-EP4 in the secretory portion of eccrine and apocrine glands and in follicular germinative cells at the lower end of catagen hairs of normal skin tissue. All BCC samples tested were positive. Of the Bowen type SCCIS samples, 26.3% reacted positively (at least 5% positive staining of neoplastic cells). In 3/76 cases (3.9%) more than 50% of the tumor cells expressed Ber-EP4. Conclusion We conclude that Ber-EP4 expression is not always helpful to distinguish between Bowen type of SCCIS and BCC, as Ber-EP4 expression in Bowen type SCCIS is not infrequent.
Gesehen am 30.04.2020